Events, States and Times : an essay on narrative discourse in English. - Altshuler, Daniel, 1981- (De Gruyter, 2016)
This monograph investigates the temporal interpretation of narrative discourse in two parts. The theme of the first part is narrative progression. It begins with a case study of the adverb 'now' and its interaction with the meaning of tense. The case study motivates an ontological distinction between events, states and times and proposes that 'now' seeks a prominent state that holds throughout the time described by the tense. Building on prior research, prominence is shown to be influenced by principles of discourse coherence and two coherence principles, NARRATION and RESULT, are given a formally explicit characterization. The key innovation is a new method for testing the definitional adequacy of NARRATION and RESULT, namely by an abductive argument. This contribution opens a new way of thinking about how eventive and stative descriptions contribute to the perceived narrative progression in a discourse. The theme of the second part of the monograph is the semantics and pragmatics of tense. A key innovation is that the present and past tenses are treated as scalar alternatives, a view that is motivated by adopting a particular hypothesis concerning stative predication. The proposed analysis accounts for tense in both matrix clauses and in complements of propositional attitudes, where the notorious double access reading arises. This reading is explored as part of a corpus study that provides a glimpse of how tense semantics interacts with Gricean principles and at-issueness. Several cross-linguistic predictions of the analysis are considered, including their consequences for the Sequence of Tense phenomenon and the Upper Limit Constraint. Finally, a hypothesis is provided about how tense meanings compose with temporal adverbs and verb phrases. Two influential analysis of viewpoint aspect are then compared in light of the hypothesis. The monograph is directed at graduate students and researchers in semantics, pragmatics an.